2017
DOI: 10.1161/atvbaha.117.309444
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotonic Steroids Stimulate Macrophage Inflammatory Responses Through a Pathway Involving CD36, TLR4, and Na/K-ATPase

Abstract: Objective Circulating levels of cardiotonic steroids (CTS) are elevated in various chronic inflammatory conditions, but the role of CTS in inflammation remains largely unknown. We have previously shown that the CTS ouabain stimulates pro-inflammatory responses in murine macrophages. In this study, we aim to explore the mechanism how CTS induce pro-inflammatory responses in primary murine and human macrophages. Approach and Results Using both murine peritoneal macrophages and human monocyte-derived macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
0
24
1
1
Order By: Relevance
“…Over the last five years, many studies have suggested a relationship between CTS and inflammation. There is some evidence that circulating levels of CTS are elevated during the inflammatory response [ 16 ] and many studies have linked specific cardiac glycosides to a proinflammatory response. Others have shown evidence of CTS inducing an anti-inflammatory response.…”
Section: Cts Nka and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last five years, many studies have suggested a relationship between CTS and inflammation. There is some evidence that circulating levels of CTS are elevated during the inflammatory response [ 16 ] and many studies have linked specific cardiac glycosides to a proinflammatory response. Others have shown evidence of CTS inducing an anti-inflammatory response.…”
Section: Cts Nka and Inflammationmentioning
confidence: 99%
“…This article will also highlight new developments in what is known about molecular partners of the NKA which help mediate these trade-off pathways. Further, while NKA ligands, such as CTS were first recognized as regulators of renal sodium transport and arterial pressure [ 14 , 15 ], recent findings have highlighted mechanistic links by which CTS modulate interactions of molecular partners with the NKA, especially as this pertains to modulation of immunity, inflammation, and fibrosis [ 16 , 17 , 18 ]. The objective of the present review is to examine the molecular mechanisms of CTS as they relate to these inflammatory and fibrotic processes.…”
Section: Introductionmentioning
confidence: 99%
“…In various chronic inflammatory conditions, circulating cardiotonic steroids are elevated that are capable of stimulating a proinflammatory response in murine and human macrophages. This process involves ouabain-stimulated activation of NF-κB through a signaling complex of Na/K-ATPase, CD36, and TLR4, leading to increases in proinflammatory cytokines MCP-1, TNF-α, IL-1β, and IL-6 [ 49 , 50 , 51 ].…”
Section: Na/k-atpase Signaling and Reactive Oxygen Species (Ros): mentioning
confidence: 99%
“…Although CGs also decrease the intracellular K + , their exact role in macrophage activation and death is more controversial, presumably because of the distinct sensitivity of murine Na + ,K + -ATPase to CGs (Perne et al, 2009;Price and Lingrel, 1988) and the potential implication of Na +, K + -ATPase in signalling events independently of ion transport (Cavalcante-Silva et al, 2017). In human PBMCs, monocytes and macrophages, nanomolar concentrations of ouabain stimulates pro-inflammatory cytokine expression, including IL-1β and TNF through NF-κB (Chen et al, 2017;Foey et al, 1997;Matsumori et al, 1997;Teixeira and Rumjanek, 2014) but only recent reports linked CG-induced cytokine release to inflammasome-mediated cell death (i.e. pyroptosis) (Kobayashi et al, 2017;LaRock et al, 2019).…”
Section: Introductionmentioning
confidence: 99%